What do we know from the transcriptomic studies investigating the interactions between plants and plant growth-promoting bacteria? - Mukherjee, Arijit (Frontiers in Plant Science, 2022)
Major crops such as corn, wheat, and rice can benefit from interactions with various plant growth-promoting bacteria (PGPB). Naturally, several studies have investigated the primary mechanisms by which these PGPB promote plant growth. These mechanisms involve biological nitrogen fixation, phytohormone synthesis, protection against biotic and abiotic stresses, etc. Decades of genetic and biochemical studies in the legume-rhizobia symbiosis and arbuscular mycorrhizal symbiosis have identified the plant and microbial signals regulating these symbioses. Furthermore, genetic studies in legumes have identified the host genetic pathways controlling these symbioses. But, the same depth of information does not exist for the interactions between host plants and PGPB. For instance, our knowledge of the host genes and the pathways involved in these interactions is very poor. However, some transcriptomic studies have investigated the regulation of gene expression in host plants during these interactions in recent years. In this review, we discuss some of the major findings from these studies and discuss what lies ahead. Identifying the genetic pathway(s) regulating these plant-PGPB interactions will be important as we explore ways to improve crop production sustainably.